Knowledge of mothers about oral health in childhood - Luciane Campos Gislon; Elisabete Rabaldo Bottan; Camila Oselame Staimbach; Carolyne Rafaeli (Faculdade Meridional IMED, 2017)
Objective: To evaluate the knowledge about oral health in a group of mothers of different socioeconomic conditions. Methods: The cross-sectional descriptive study involved 187 mothers of children enrolled in the municipal school system, in a municipality in the west of Santa Catarina. The data collection tool was a questionnaire. For the classification of socioeconomic condition was adopted the indicator of the Brazilian Association of Research Companies - 2014. The chi-square test was used to analyze the association between the knowledge level and socioeconomic situation. Results: The mean age of the group of mothers/guardians that comprised the study was 33.5 years. Regarding the socioeconomic condition, 24% belonged to class A, 52.5% to class B and 23.5% to class C. The number of children ranged from 1 to 4 per mother. With regard to oral health information sources, the participants of all socioeconomic classes cited the Dental Surgeon more frequently. Good knowledge was the most frequent in all socioeconomic categories; however, this frequency reduces in function of socioeconomic status (p≤0.002). The worst performance of the group was in relation to the item on the recommended age for the child to perform their oral hygiene without the accompaniment of an adult. The best performance was for the question about the influence of diet on oral health. Conclusion: In the investigated group it was evidenced that the socioeconomic situation interfered in the level of knowledge.